Cross-Modal Perception of Noise-in-Music: Audiences Generate Spiky Shapes in Response to Auditory Roughness in a Novel Electroacoustic Concert Setting - Liew, Kongmeng; Lindborg, PerMagnus; Rodrigues, Ruth; Styles, Suzy J. (Frontiers in Psychology, 2018)
Noise has become integral to contemporary music aesthetics. In this paper, we define noise as sound that is high in auditory roughness, and examine the effect of noise on cross-modal mapping between sound and visual shape in participants. In order to preserve the ecological validity of contemporary music aesthetics, we developed Rama, a novel interface, for presenting experimentally controlled blocks of noise that form part of the sound design of a multimedia performance with live musicians, and also allows data to be actively collected from audience interaction. Audience members listened to noisy sounds, and collectively voted to create the shape of a visual graphic, presented as part of the audio-visual performance. The results of the concert setting were replicated in a controlled laboratory environment to corroborate the findings. Results show a consistent effect of auditory roughness on shape design, with rougher sounds corresponding to spikier shape. We discuss the implications, as well as evaluate the audience interface.